Effects of Different Clay's Percentages on Improvement of Sand-Clay Mixtures with Microbially Induced Calcite Precipitation. Issue 9 (21st October 2019) - Sun, Xiaohao; Miao, Linchang; Chen, Runfa
Abstract: Microbially induced calcite precipitation (MICP) is currently appraised for the improvement of sandy soils, but only few studies use it to improve sand-clay mixtures. The effect of contents of kaolin clay and the effect of ions in kaolin clay on bacterial urease activity and productive rates for calcium carbonate were studied. Moreover, sand solidification tests were conducted and the solidifying effects of MICP for sand-clay mixtures were evaluated. The results show that adding kaolin clay has an inhibitory effect on the urease activity of bacteria, and adding too many kaolin clays also decrease the productive rates for calcium carbonate. With adding Al2 O3 or FeCl3, urease activity both decreases and it becomes lower with adding more Al2 O3 or FeCl3 . The permeability of sand columns all decreased gradually with MICP curing. With more kaolin clay, the increasing range of bacterial utilization rates of those with larger particle sizes is bigger. The maximum productive rate for calcium carbonate of samples with smaller particle sizes exists in sample with 5% of kaolin clay while other samples with 7.5% of clay have more calcium carbonate. Sand columns with different sand particle sizes have different suitable amounts of added kaolin clays for MICP solidification.